2016
DOI: 10.1097/aud.0000000000000268
|View full text |Cite
|
Sign up to set email alerts
|

Description of Adults Seeking Hearing Help for the First Time According to Two Health Behavior Change Approaches: Transtheoretical Model (Stages of Change) and Health Belief Model

Abstract: The main predictors of stages of change in first-time help seekers were reported participation restrictions and duration of hearing difficulty, with constructs from the health belief model also explaining some of the variance in stages of change scores. The transtheoretical model and the health belief model are valuable for understanding hearing health behaviors and can be applied when developing interventions to promote help seeking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 37 publications
1
38
1
Order By: Relevance
“…All measures are described below, with additional information in the source reference and in Saunders et al (2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All measures are described below, with additional information in the source reference and in Saunders et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…In the initial stages of this work, we examined the attitudes and beliefs of adults who had sought hearing help for the first time (Saunders et al, 2016). We determined that degree of hearing impairment was associated with the constructs of the TTM and the HBM, and that participation restriction, degree of hearing impairment, and the HBM constructs of perceived benefits, barriers and self-efficacy were significant predictors of stages of change.…”
mentioning
confidence: 99%
“…The model of hearing health belief can be applied in testing the possibility of changing behavior of subjects related to hearing health, as well as predicting the future of hearing conditions (Pronk et al 2017). Saunders et al (2016) pointed out that people with better hearing have higher perceived levels of sensitivity, severity, and benefits that are important for hearing loss prevention.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Combining the two models, Saunders et al found that increasing self-efficacy, conveying perceived benefit, and providing a cue to action were critical constructs and should be incorporated into interventions. 24 Self-efficacy is a commonly targeted component in improving the uptake of a given health behavior, particularly when the behavior includes use of technology by an older adult, such as hearing aids, and can be enhanced through training. 25,26 Beyond self-efficacy, social support is associated with increased help-seeking, where significant others can act as a cue to action, and has also been associated with greater hearing aid satisfaction.…”
Section: Hearing Healthcare As a Health Behaviormentioning
confidence: 99%